The Gender Inequality and Participation of Women in Stem Fields - Xhindi, Teuta; Gjika, Ira (UNWE Yearbook, 2023)
It is both important and interesting to highlight the role of women in the general development of countries nowadays. Beyond the efforts done by the policymakers and the civil society towards empowering and inclusion of women in political, social, and economic life, Albania is amongst those countries that have a long road ahead to really improve the gender equality situation.This paper studies the relationship between the Gender Inequality Index and the number of women graduates in the STEM field, trying to reveal what kind of correlation exists between them. The instruments used are descriptive statistics and correlation analysis.The main result is: there is a statistically significant linear relationship between the two variables.